Impact of the hybrid reactive power compensator on the power grid used a fuzzy PI regulator - Abdelkader Rahmouni (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The work presented in this article is a contribution to the problem of controlling reactive powers and voltages in an electrical network. Among these control tools, the static reactive power compensator (SVC) was chosen because of its simplicity of control. SVC is one of the Alternative Flexible Current Transmission Systems (FACTS) devices which help to solve the problems encountered in the operation of electrical networks, either on the distribution side or on the transport side. To increase its compensation efficiency in the face of harmonic currents which cause voltage distortion, we have introduced a three-phase harmonic filter. This new hybrid SVC is used to control the reactive power, the voltage and in addition to reduce the voltage distortion and the correction of the power factor in the electrical energy transport network. In order to improve its efficiency, two voltage regulation systems have been chosen in the control system for this compensator, the fuzzy PI regulator and the PIP regulator.